Toward Better Physical Education Outcomes Assessing the Effectiveness of Blended Learning in Middle School Physical Education using TreeSoft Set - Yuanyuan Qi (Neutrosophic Sets and Systems)
Physical education (PE) teaching methods have changed because of blended learning, which combines traditional in-person training with online learning resources. The implementation of blended learning in physical education in middle schools, when kids are going through major developmental changes, necessitates a thorough assessment to ascertain its actual efficacy. By looking at both technology integration and physical activity outcomes, this study investigates the critical elements that make blended learning in middle school physical education settings successful. The study assesses how environmental conditions, instructor involvement, student engagement, and instructional design affect overall learning effectiveness using a multicriteria assessment approach. We use the TreeSoft set to divide the criteria and sub criteria as Tree and we compute the criteria weights in each local criteria and in global criteria. We rank the alternatives using the WSM method. For educators and policymakers looking to maximize physical education in a changing digital educational environment, the findings provide insightful information.